Can Richer Metadata Rescue Research?. Issue 1 (31st May 2018) - Kemp, Jennifer; Dean, Clare; Chodacki, John
ABSTRACT: This article reflects the discussion of metadata challenges faced by the scholarly communications community at this year's NASIG conference. Exploring the potential opportunities for the enrichment of metadata, we consider the evolving role of the metadata librarian and review opportunities for all librarians to contribute to an important new collaboration for the wider benefit of scholarly communications. The Metadata 2020 collaboration was the context for the session, which focused on barriers to progress and the role of nonbibliographic metadata in the evolution of library services.